Large Eddy Simulation of Turbulent Flow and Inclusion Transport during Filtration of Liquid Steel inside Open‐Cell Ceramic Foams. Issue 2 (29th September 2021) - Demuth, Cornelius; Werzner, Eric; Dudczig, Steffen; Aneziris, Christos G.; Ray, Subhashis
Abstract : The present numerical investigation is conducted to improve the understanding of the physical processes, encountered during the filtration of steel melt. For this purpose, the process conditions in a pouring experiment are considered. The effects of increasing either the superficial melt velocity or the pore count of the filter are studied. The turbulent flow is modeled using the large eddy simulation in the context of the lattice Boltzmann method and the motion of nonmetallic inclusions is predicted using discrete Lagrangian particle tracking. The simulations show that turbulent flow develops as the melt advances through the filter, with the length scale of the smallest flow structures lying in the same order as the particle size. The pressure drop and the filtration coefficient are found to agree with the previous studies. Abstract : Herein, the use of large eddy simulation for filtration of molten steel inside porous foams to improve the understanding of the physical processes is demonstrated. The results, obtained for different pore counts and flow velocities, show that turbulent flow develops as the melt advances through the filter, with smallest scales of the order of the particle size.